Demineralized Bone Matrix Carriers and their Clinical Applications: An Overview - Zhang, Hao; Yang, Li; Yang, Xiong‐gang; Wang, Feng; Feng, Jiang‐tao; Hua, Kun‐chi; Li, Qi; Hu, Yong‐cheng (Orthopaedic surgery, 2019)
Reconstruction of massive bone defects is challenging for orthopaedic clinicians, especially in cases of severe trauma and resection of tumors in various locales. Autologous iliac crest bone graft (ICBG) is the “gold standard” for bone grafting. However, the limited availability and complications at donor sites resulted in seeking other options like allografts and bone graft substitutes. Demineralized bone matrix (DBM) is a form of allograft using acidic solution to remove mineral components, while leaving much of the proteinaceous components native to bone, with small amounts of calcium‐based solids, inorganic phosphates, and some trace cell debris. It is an osteoconductive and osteoinductive biomaterial and is approved as a medical device for use in bone defects and spinal fusion. To pack consistently into the defect sites and stay firmly in the filling parts, DBM products have various forms combined with biocompatible viscous carriers, including sponges, strips, injectable putty, paste, and paste infused with chips. The present review aims to summarize the properties of various kind of viscous carriers and their clinical use combined with DBM in commercially available products. Given DBM'mercially available products. Given DBM;s long clinical track record and commercial accessibility in standard forms, opportunities to further develop and validate DBM as a versatile bone biomaterial in orthopaedic repair and regenerative medicine contexts are attractive.